Processos de emergência e de definição da homofobia como um problema público no Brasil - Santos, Sérgio Lima dos (2018)
The problem of violence against lesbians, gays, bisexuals, transvestites, transsexuals and transgenders (LGBT) has been increasingly taken as the object of denunciations, as well as legal and political disputes in Brazil. The controversies lie, on the one hand, in the defense of the typification and criminalization of violence as a way of strengthening democracy and respecting sexual differences and human dignity. On the other hand, in the thesis that the constitution of a specific law which aims to penalize, in the criminal sphere, prejudices, crimes and violence against LGBT violates the constitutional principles that guarantee the free manifestation of thought concerning religious belief, philosophical conviction or those who disagree with these sexualities. All this problematization and social visibility of violence against LGBT people have intensified since 2006, as a result of the Bill 122/2006 (PLC 122/06), also called the anti-homophobia law, which aimed to criminalize any kind of prejudice related to gender, sexual orientation and gender identity. In order to understand the social conditions which promote an anti-homophobia fight in the Brazilian scenario, this thesis aims to analyze the processes of emergency, definition and construction of the social problem of violence against LGBT as a public and political problem in the country. For that, we developed a qualitative research, with an exploratory and descriptive approach, based on a bibliographical and documentary analysis, focusing on the Sociology of Public Problems, as well as other theoretical and methodological contributions. Even knowing that PLC 122/06 has promoted broad visibility to the problem of homophobia, research has shown that the current centralization on the agenda around criminalization neglects a set of problematic situations that have led, in different social, political and cultural contexts, to collective experiences which built multiple definitions of homophobia in Brazil and contributed to the construction of this cause as a public and political problem.